MALNUTRITION IN CHILDREN: UNDERSTANDING CAUSES, CONSEQUENCES, AND EVIDENCE-BASED PREVENTION STRATEGIES (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2026)
Childhood malnutrition remains one of the most pressing public health challenges of the twenty-first century, affecting millions of children across high-income, middle-income, and low-income nations alike. The condition encompasses a spectrum of nutritional disorders, including undernutrition manifested as stunting, wasting, and micronutrient deficiencies, as well as the rising burden of overweight and obesity among pediatric populations. The first two years of life represent a particularly vulnerable window during which inadequate nutrition can cause irreversible damage to physical growth, cognitive development, and immune function. This narrative review examines the multifactorial etiology of childhood malnutrition, analyzes current global burden data, discusses the short-term and long-term health consequences, and evaluates evidence-based prevention and treatment interventions. By synthesizing recent findings from the World Health Organization (WHO), the United Nations Children’s Fund (UNICEF), and peer-reviewed epidemiological literature, this article provides a comprehensive overview intended for healthcare professionals, policymakers, and public health practitioners committed to achieving the Sustainable Development Goals related to child survival and well-being.